The Correlation Between Marketing Elements and Consumer Purchase Interest at Suzuki Persada Car Dealer - Buchori Buchori; Dede Dede; Putri Sandora; Nani Lina Wati (Utan Kayu Publishing, 2024)
This study aims to evaluate the impact of each element of the marketing mix on consumer purchase interest, providing valuable insights for Suzuki Persada Car Dealer in developing more effective marketing strategies. The data collection techniques for this research include questionnaires and documentation. The sample in this study consists of 100 consumers interested in purchasing a car at the Suzuki Persada car dealer in Lampung.The results of this study are: (1) the questionnaire instrument used is valid, as the calculated R value is greater than 0.300, (2) the reliability test results, which determine the accuracy of the measuring instruments used, show values of 0.717 for product quality, 0.762 for price, 0.892 for place, 0.745 for promotion, and 0.751 for purchase interest, all of which are greater than the minimum value of 0.6, (3) product quality significantly influences purchase interest by 59.1%, (4) price significantly influences purchase interest by 61.7%, (5) place significantly influences purchase interest by 43.9%, (6) promotion significantly influences purchase interest by 51.5%, (7) product quality, price, place, and promotion significantly influence purchase interest by 80.2%, with the remaining influence coming from other factors